STILE KEPENGARANGAN TENAS EFFENDY DALAM TUNJUK AJAR MELAYU - Sri Rahayu; Alber; Viora (Perspektif Pendidikan dan Keguruan, 2020)
Literary works are classified as works of imagination in the form of fictional or imaginary experiences. The messages to be conveyed through literary works must be creative so that they appear attractive to read and listen to, so it is necessary to have a stile from the authorship itself to make his work beautiful and attractive. There are many ways to enjoy, understand and appreciate the work of the author Tenas Effendy, one of which is by studying the Stile of Tenas Effendy's authorship in Tunjuk Ajar Melayu. This study aims to analyze and interpret Tenas Effendy's stile authorship in Tunjuk Ajar Melayu. This needs to be examined because the existence of a literary work can be seen from how the author packs his work so that he can create his own stile from the author's side. The method used in this research is content analysis method. The source of data in this research is Tunjuk Ajar Melayu Karya Tenas Effendy in 2013 which has been recorded. The data collection technique is done by applying the hermeneutic technique. After the author of the analysis, Tunjuk Ajar Melayu by Tenas Effendy has a unique and distinctive authorship stile seen from the stylistic aspect, namely the stile as a pack of thoughts, the stile as a deviation from linguistic norms and the stile as a collection of personal characteristics.